Unpacking the Implication of the COVID-19 Pandemic for Small Businesses in Lebak Regency, Banten Province - Salampessy, Yudi L.A; Suherna; Gunawan, Gugun (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
In recent times, small businesses have been recognized as a significant component of national economies, as evidenced by their resilience during the monetary crisis faced by Indonesia in 1999. However, the COVID-19 pandemic has presented a unique challenge due to the invisible nature of the virus, its social transmission, and the resultant threats to human safety. Small businesses have undergone several changes, including altered consumer behavior, production patterns, and product marketing, primarily due to their reliance on crowds and direct interactions between sellers and buyers. Consequently, many small businesses have either shut down or faced difficulties in maintaining their sustainability. To gain insights into the implications of the COVID-19 pandemic for small business actors, we conducted a qualitative phenomenological study in Lebak Regency, Banten Province. Our findings suggest that the informants viewed the pandemic as a crisis that tested their adaptive capacity. This capacity encompassed not only the ability to adjust to changing economic conditions but also a sense of gratitude for the outcomes of their business activities. The quality of these attributes together determined the sustainability of their business.